Transcriptome Analysis Reveals Differential Expression of Genes Regulating Hepatic Triglyceride Metabolism in Pekin Ducks During Dietary Threonine Deficiency - Jiang, Yong; Xie, Ming; Fan, Wenlei; Xue, Jiajia; Zhou, Zhengkui; Tang, Jing; Chen, Guohong; Hou, Shuisheng (Frontiers in Genetics, 2019)
Previous reports demonstrated that dietary threonine (Thr) deficiency increased hepatic triglyceride accumulation of Pekin ducks, which results in fatty liver disease and impairs the hepatic function. However, the underlying molecular mechanisms altered by dietary Thr deficiency are still unknown in Pekin ducks. For identification of its underlying molecular changes, 180 one day old ducks were divided into three groups, including Thr deficiency group (Thr-D), Thr sufficiency group (Thr-S), and pair-fed group (Pair-F) fed Thr sufficient diet with similar daily feed intake with Thr-D group. The results showed that Thr-D and Pair-F groups had similar feed intake, but the weight gain and body weight in Thr-D group were lower than that in Pair-F group. The feed intake, weight gain, and body weight in Thr-D and Pair-F groups were lower than that in Thr-S group. Thr-D reduced the abdominal fat percentage, but increased hepatic triglyceride content compared with Thr-S and Pair-F groups. Pair-F reduced hepatic contents of C15:0, C17:0, C18:0, C20:0, C20:4n6, and C22:0, and also reduced total fatty acid, saturated fatty acid, and unsaturated fatty acid contents, compared with Thr-D and Thr-S groups. Thr-D increased hepatic contents of C6:0, C17:1, C18:3n6, C20:0, C20:1n9, and C22:2, and reduced the contents of c18:2n6t, and c23:0 compared with Thr-S group. Transcriptome analysis in liver sample indicated that Thr-D upregulated genes expression related to fatty acid and triglyceride synthesis, and downregulated genes expression related to fatty acid oxidation and triglyceride transport. Gene ontology analysis showed that more genes was enriched in lipid-related processes and molecular function in Thr-D vs Thr-S, and Thr-D vs Pair-F groups than that in Pair-F vs Thr-S group. KEGG Pathway analysis showed that differentially expressed genes were enriched in signal transduction, immune, hormone, lipid and amino acids metabolism pathway. It was concluded that Thr-D increased hepatic triglyceride and fatty acid accumulation via increasing fatty acid and triglyceride synthesis, and reducing fatty acid oxidation and triglyceride transport. These findings provide novel insights into our understanding of molecular mechanisms of liver caused by dietary Thr deficiency in ducks.